The Role of Computer Technology in Detection of Forged Signatures Having Overlapping Features Case Report - Melez, İpek Esen; Melez, Deniz Oğuzhan; Şahin, Muhammed Feyzi; Gürler, Ahmet Selçuk; Tırtıl, Lale (The Bulletin of Legal Medicine, 2015)
Signature is a handwriting type which reflects the personal characteristics and which is legally accepted to be exclusive. Various methods can be used for signature forgery and copying through carbon paper use is one of these methods. In this study, to show ‘overlapping’ with the method of superimposition of the signatures in computer media through analyzing the case of a signature forgery which includes the method of copying through carbon paper use and to discuss the role of computer technologies together with the differential diagnosis of ‘overlapping’ in document examination have been aimed. With regards to contemporary document examination expertise, besides personal experience, also computer technologies are becoming important in the analysis. In the evaluation of forgery components between two signatures or signature groups being identical to a degree which seems to be impossible in the nature of things (overlapping), this case and the way of its analysis is found
Keywords: document examination; signature examination; computer technology; superimposition; overlapping